LGBT dalam al-Quran: Kajian Tematik Tafsir al-Maraghi Karya Ahmad bin Mustafa al-Maraghi - Imas Amasiroh, Imas; Imam Bashori, Imam (Mahad Aly Al Fithrah Press, 2020)
The speciality of Quran certainly can’t be released by the process of descent of Quran to the prophet Muhammad (peace be upon him) gradually. However, the content of Quran by Moslem still understood have no contradictions with each other. The verses of Quran are not all explained in detail and not all can be understood just textually, because there are many verses of the Qur'an still have a abstract meaning and need to be interpreted more deeply, in order can take a law or wisdom that can be understood and practice. Expect of Quran to can answer all of problems of life in modern era that are often made sensational. Like the rise of same-sex relationship news in developed countries, it has even become a community known as LGBT. The study aims to study LGBT in the Quran by means of Tafsi>r al-Mara>ghi>. This study is library research, and collects data on LGBT according to Quran thematically. Meanwhile, in this research focus on al-Maraghi's interpretation. The result from this study is LGBT can be called liwa>t, which means doing deed like the deed of the prophet Lut. This kind of deed is very contradiction with demands of fitrah, which can result what is termed 'uqubatu al-fitrah (fitrah sanctions). Thus, LGBT is among others that can be called fa>hishah in Quran.